Investigating on effect of fan blades angle of a water-cooled air conditioner on its performance through CFD analysis - Yingying Zhang (Journal of Applied Science and Engineering, 2025)
Most studies conducted in the indoor unit of water-cooled air conditioners focus on increasing its efficiency and reducing its temperature. The purpose of this study is to conduct a numerical simulation of a centrifugal fan with forward blades using the CFD method and investigate the effects of changing the angle of the blades on the performance of the desired fan. The velocity and pressure distributions of the fan are obtained by solving momentum equations and ensuring continuity with the fluid flow inside the fan. An investigation was conducted on four different angles of ±5, ±10 and ±15 degrees. The 3D flow of incompressible viscous fluids in the production domain was simulated using ANSYS CFX software. We consider the water cooler environment to be a porous one. Based on the simulation results, pressure and velocity contours are displayed around the angle of installation of the blower blade in the indoor unit. The gradients produced on the blower blade in four modes were compared. Four blades with different angles have been compared in terms of their speed at the cooler outlet. According to the results, the cooler output produces the best performance at an angle of -15 degrees.